2011
DOI: 10.1017/s1751731111001066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary lipids and Clostridium butyricum on serum lipids and lipid-related gene expression in broiler chickens

Abstract: The effect of dietary lipids and Clostridium butyricum supplementation on circulating lipids and the transcription of selected genes involved in lipid metabolism were investigated in broiler chickens. One hundred and sixty-day-old broilers (Arbor Acres) were divided into four treatment groups in a 2 3 2 factorial arrangement and fed four diets with two lipid sources (soybean oil or fish oil) and two levels of C. butyricum (0 or 5 g/kg) for a period of 6 weeks. Serum concentrations of total cholesterol and low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 37 publications
5
20
0
Order By: Relevance
“…Barter et al (2010) reported that a link may exist between the changes in HDL-C and TG, but they found no apparent relationship between LDL-C reduction and HDL-C increase. However, Zhang et al (2011) and Zhao et al (2013) observed that diet containing Clostridium butyricum and Enterococcus faecium exerted no effect on the concentrations of TG, TC, HDL-C, and LDL-C in broiler sera. Meanwhile, the serum INS levels were enhanced by C .…”
Section: Discussionmentioning
confidence: 98%
“…Barter et al (2010) reported that a link may exist between the changes in HDL-C and TG, but they found no apparent relationship between LDL-C reduction and HDL-C increase. However, Zhang et al (2011) and Zhao et al (2013) observed that diet containing Clostridium butyricum and Enterococcus faecium exerted no effect on the concentrations of TG, TC, HDL-C, and LDL-C in broiler sera. Meanwhile, the serum INS levels were enhanced by C .…”
Section: Discussionmentioning
confidence: 98%
“…PPAR-α, as a member of nuclear receptors, is highly expressed in the liver and plays an important role in regulating glucose and lipid metabolism or enhancing the related-gene expression in fatty acid oxidation (Lee et al, 1995;Zhang et al, 2011;Huang et al, 2013). LPL, on the other hand, catalyzes triglycerides from circulating chylomicron and very low-density lipoprotein to generate fatty acids and glycerol for tissue utilization or storage (Zhao et al, 2013).…”
Section: Effect Of Cottonseed Meal Fermented With Yeast On the Lipid-mentioning
confidence: 99%
“…Apart from being an important macronutrient, dietary fat has recently gained much prominence for its role in regulating gene expression in poultry (Royan et al 2011;Zhang et al 2011;Jing et al 2013). LPIN1, LPIN2, WDTC1/ADIPOSE, and △-6 fatty acid desaturase (FADS2) were reported as lipid metabolism genes in human and mouse.…”
Section: Introductionmentioning
confidence: 99%